A importância do manual do professor na transposição didática da matemática - Costa, José Roberto (2008)
There is a great distance between the knowledge of Mathematical Science that the teacher studies at graduation and the knowledge that he will teach the students. It is the teacher's task to transpose this distance, and to assist him in the pedagogical action of transforming the educational scientific knowledge in the taught knowledge, there are the Student's Book and the respective Teacher's Manual, this latter is placed at his disposal by the author of the book, with the intent of explaining his pedagogical proposition. This work investigated the importance of the Teacher's Manual in didactic Mathematical transposition in the final years of Secondary school. Besides the treatment of didactic transposition in Mathematics, it made from the own theoretical references of French didactic in Mathematics, the historical aspects of Mathematics Teaching and the Didactic Book and the transformation of Teacher's Manual, which refers to the form and the content from the 1970 decade, they have been studied to the contextualization of research. Methodologically, it was opted for a qualitative approach, with interviews made to ten teachers, which were subsidized by the results of a previous implementation of a questionnaire answered by 56 Mathematics teachers from the Secondary school, who are entailed to the Maringá's Núcleo Regional de Ensino. The study evidenced that a part of many teachers don't use the Teacher's Manual, and it pointed some indications that explained the reason of this fact, among these: a classroom reality very different from the theoretical reality of the Manual, according to indiscipline, disinterest and a lack of students basis, an ineffective contact in teaching practice between the future teachers and the Teacher's Manual and over-confidence of experienced teachers who judge it is more appropriated for teachers in the beginning of professional carrier.